Implementation of Zakat Application in Improving the Performance of Amil Zakat Agency in Jelapat Village, South Barito District - Norika Pitasari; Raldi, Raldi; Rahimah, Annisa; Riskiah, Mudah; Rahmadayanti, Nurul; Aprilia, Rida; Yuni Purwanti, Devi; Edyawati, Lastri; Lukman Hakim, Muhammad; Warman, Taufik (Amala Jurnal Pengabdian Kepada Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) is a higher education program in Indonesia that aims to integrate science and community service. The program is mandatory for students to participate in social activities outside the campus. KKN began in the 1971/1972 academic year and was initially implemented by several well-known universities in Indonesia. The main concept of KKN is to allow students to experience the social, economic, and cultural problems of rural communities. The program has grown significantly and received government support to support development at the village level. KKN in Jelapat Village, South Barito Regency, Central Kalimantan, focused on the implementation of a zakat application to improve the performance of the Amil Zakat Agency in the region. The application improves the efficiency, transparency, and effectiveness of zakat management. Zakat application training helps mosque/musholla administrators to master technology in zakat management, reduce errors in data management, and report results accurately. Transparency in the management of zakat funds is also improved, strengthening public trust in the Amil Zakat Agency. The agency becomes more efficient in managing zakat recipient data and reporting the results of zakat collection, allowing it to focus on social programs. In addition to efficiency and transparency benefits, the zakat application training also strengthens the role of mosques/musholla in zakat collection and management. Mosques/mushollas, as centers of social and religious activities, play a strategic role in collecting zakat. In general, the training has a positive impact on zakat management and increases the social and economic benefits of zakat in the local community. The results showed a significant improvement in the efficiency and transparency of zakat management and strengthened the role of mosques/musholla in this process. Although challenges remain, the zakat application training is an important step in increasing the benefits of zakat in the local community.